2024
DOI: 10.1088/2632-959x/ad1d02
|View full text |Cite
|
Sign up to set email alerts
|

Niosomes modified with a novel pH-responsive coating (mPEG-OA) enhance the antibacterial and anti-biofilm activity of vancomycin against methicillin-resistant Staphylococcus aureus

Nawras Osman,
Calvin A Omolo,
Mohammed A Gafar
et al.

Abstract: Surface functionalization of nanoparticles has shown potential in enhancing the efficacy of antibiotic-loaded nanosystems against drug-resistant bacteria. The objective of this study was to synthesize and characterize an acid-cleavable pH-responsive polymer from methoxy polyethylene glycol and oleylamine (mPEG-OA) to surface modify vancomycin (VCM)-loaded niosomes and to evaluate their antibacterial and anti-biofilm effectiveness against methicillin-resistant Staphylococcus aureus (MRSA). The novel mPEG-OA-coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…According to their results, a significant anti-biofilm activity was also found against P. aeruginosa biofilms through incorporation of positively charged agents into niosomal formulation ( P -value < 0.05). Also, another conducted study revealed that of niosomal optimization through surface modification with PEGylatation improved the anti-bacterial and anti-biofilm activities of vancomycin-encapsulated niosomes against S. aureus strains ( P -value < 0.05) 43 . The confirmatory results were also reported in the published studies on liposomal formulations.…”
Section: Discussionmentioning
confidence: 98%
“…According to their results, a significant anti-biofilm activity was also found against P. aeruginosa biofilms through incorporation of positively charged agents into niosomal formulation ( P -value < 0.05). Also, another conducted study revealed that of niosomal optimization through surface modification with PEGylatation improved the anti-bacterial and anti-biofilm activities of vancomycin-encapsulated niosomes against S. aureus strains ( P -value < 0.05) 43 . The confirmatory results were also reported in the published studies on liposomal formulations.…”
Section: Discussionmentioning
confidence: 98%
“…The antibacterial properties of several niosomal drug delivery systems against different bacterial pathogens, including Staphylococcus epidermidis , Bacillus subtilis , Pseudomonas aeruginosa , Klebsiella pneumoniae , Acinetobacter baumannii , and Escherichia coli were approved [ 31 33 ]. Also, the results of some experiments exhibited that niosome nanoparticles, as a powerful drug delivery system, hold promise for solving serious challenges related to S. auras [ 34 36 ]. However, the present research aims to evaluate the antibacterial activity of VAN-niosome against MRSA clinical strains with emphasis on cytotoxicity study on human foreskin fibroblast (HFF) cell line.…”
Section: Introductionmentioning
confidence: 99%